Pyrolysis of Corn Residues: Kinetic Analysis using Discrete Distributed Activation Energy Model. (June 2018) - Onsree, T; Sittisun, P; Sasaki, R; Tippayawong, N
Abstract: Agro-residues are usually generated in large amount. These biomass materials may be utilized as renewable energy source via thermochemical conversion processes. Knowledge on kinetic of thermal decomposition behavior of biomass is important in reactor design and thermal process optimization. In this work, thermogravimetric (TG) data (35 to 900°C, at heating rates of 5 to 50°C/min) from pyrolysis of corn residues was analyzed using discrete distributed activation energy model (DAEM). Prediction accuracy of the simulated data was verified by comparing experimental with calculated data of conversion at selected heating rates. Kinetic parameters including activation energy and pre-exponential factor obtained from this method were found to give correct conversion curves for different heating rates simultaneously with correlation coefficients greater than 0.99, within the ranges considered. According to the discrete DAEM, variation in activation energy with conversion implied changes in mechanism during pyrolysis process. The activation energies were observed to be in the range of 100 – 120 and 80 – 180 kJ/mol for the macro-TG and typical TG analysers, respectively.